PERSPEKTIF MEDIA PRANCIS DALAM PEMBERITAAN PENCEMARAN AIR DI iNDONESIA - Wirawan Ilham Saputra; Muhammad Hasyim; Fierenziana G Junus (Institut Agama Islam Negeri Kendari, 2020)
This study aims to analyze the perspective of French media on the reporting of water pollution in Indonesia through language rhetoric. This study uses a qualitative descriptive method with an applied linguistic approach (language style). Data collection, in the form of media texts, is sourced from three French online media, namely Enviro2b, La Croix, Le Point, Les Groumerstrotters, and Liberation. The author collected news texts from the five French media that raised the theme of water pollution in Indonesia. The results of the study concluded that French online media conveyed their attitudes and views on the management of plastic waste in Indonesian waters through the use of language rhetoric, namely hyperbole, repetition, and metaphorical style. The use of repetition and hyperbole language shows the attitude and critical view of the French media towards the pollution of plastic waste in the Indonesian sea. One of the critical statements through hyperbole rhetoric is that the word 'flood' is used to describe the situation of plastic trash that floods Indonesian waters.